If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x2+12=14
We move all terms to the left:
x2+12-(14)=0
We add all the numbers together, and all the variables
x^2-2=0
a = 1; b = 0; c = -2;
Δ = b2-4ac
Δ = 02-4·1·(-2)
Δ = 8
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$
The end solution:
$\sqrt{\Delta}=\sqrt{8}=\sqrt{4*2}=\sqrt{4}*\sqrt{2}=2\sqrt{2}$$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(0)-2\sqrt{2}}{2*1}=\frac{0-2\sqrt{2}}{2} =-\frac{2\sqrt{2}}{2} =-\sqrt{2} $$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(0)+2\sqrt{2}}{2*1}=\frac{0+2\sqrt{2}}{2} =\frac{2\sqrt{2}}{2} =\sqrt{2} $
| -8=x-33 | | 12n+36=192 | | Y=(3x-7)/(5x-8) | | 8x5=35 | | d+224=531 | | v-89/9=1 | | 2×(x-4)+1=6x | | 5/24=3/8d | | n+55=82 | | n6=10 | | 6c+-14c-(-17c)-12c-(-13c)=-10 | | r-63/7=3 | | 2x+0.33x-10=4 | | 12=(a-2)3 | | x2-6=-8 | | r-26/7=3 | | 9z-(-11z)+-18z-9z=-7 | | 169=-5(7+6n)-6 | | 4x−3=3x+3 | | 4x+10+6x=30 | | 8y+48=-40 | | 5(c+2)=-10 | | 5y+2=4y+7 | | a4=8 | | -16u+15u+19u-9u-3=15 | | x4-7=-4 | | 2x+20=5-3x | | 7x×=98 | | -9k-4k-(-10)=-16 | | 5y+1y+5(y)=22 | | 4x+-2+3x+-7=-51 | | 100=20+4x |